Influence of anxiety on the presence of temporomandibular dysfunction and sleep disorders in adult patients (Research, Society and Development, 2023)
The aim of this study was to evaluate the influence of anxiety on the presence of TMD and sleep disorders in adults by using regression and correlation. The methodology applied consisted of a quantitative cross-sectional study, where 113 patients aged between 20 and 45 years, with one or more symptoms of anxiety and/or temporomandibular dysfunction and/or sleep disorders. Volunteers answered the Beck-BAI, RDC/TMD and Fletcher & Luckett questionnaires for symptom analysis. The results showed that anxiety had a statistically significant influence on all evaluated variables of TMD and sleep disorders. Thus, it was concluded that the signs and symptoms of TMD and sleep disorders are influenced by anxiety.